2002
DOI: 10.1002/jbm.10060
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and biocompatibility of alginate‐PLL capsules for immunoprotection of mammalian cells

Abstract: Transplantation of encapsulated living cells is a promising approach for the treatment of a wide variety of diseases. Large-scale application of the technique, however, is hampered by insufficient biocompatibility of the capsules. In order to get means to study factors influencing the biocompatibility of capsule for encapsulation of living cells, we have correlated the chemical composition of the surface of commonly applied alginate-PLL capsules with the biological response in rats. Capsules prepared of algina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 35 publications
4
108
0
3
Order By: Relevance
“…In previous studies we showed that especially variations in poly-L-lysine content, i.e. Ncontent, can be hold responsible for inflammatory responses [34,42]. In the present study we therefore engineered capsules with a similar N-content (Table 1).…”
Section: Surface Properties Before Implantationmentioning
confidence: 95%
See 1 more Smart Citation
“…In previous studies we showed that especially variations in poly-L-lysine content, i.e. Ncontent, can be hold responsible for inflammatory responses [34,42]. In the present study we therefore engineered capsules with a similar N-content (Table 1).…”
Section: Surface Properties Before Implantationmentioning
confidence: 95%
“…This decrease in N signal reflects a loss of PLL at the surface of high G capsules and exposure of positive charges. Free positive charges on high-G capsules are considered to be responsible for inflammatory responses and are considered to be causative for inflammatory responses to alginate-PLL capsules [34,47]. To measure possible positive charges on capsules we quantified the zeta-potential of implanted capsules at day 1 after implantation.…”
Section: Surface Properties After Implantationmentioning
confidence: 99%
“…Specifically, the challenges used to overcome the functional loss of glucose sensors, restenosis after stent implantation, and calcification induced by implantable devices are discussed. chitosan, [20][21][22] alginate, 23 hyaluronan, 24 and dextran. 25,26 Commonly used synthetic polymers include poly(lactic acid)(PLA) and poly(lactic-co-glycolic acid)(PLGA), [27][28][29][30][31][32][33] poly(ethylene glycol)(PEG), 34-36 2-hydroxy ethyl methacrylate, 33 and poly(vinyl alcohol)(PVA).…”
Section: Symposium Abstractmentioning
confidence: 99%
“…However, less cytotoxicity or inflammatory reactions (21). Alginate is the most commonly employed polymer the intraparenchymal administration is characterized by early death of grafted cells (23,29,38,44,48) and in the for cell encapsulation because of its excellent biocompatibility and an in vivo stability (6,40,53). Alginate is case of their survival they potentially differentiate in unsuitable phenotypes.…”
Section: Introductionmentioning
confidence: 99%